DUPAN-II normalisation as a biological indicator during preoperative chemoradiation therapy for resectable and borderline resectable pancreatic cancer - Shinichiro Hasegawa; Hidenori Takahashi; Hirofumi Akita; Yosuke Mukai; Manabu Mikamori; Kei Asukai; Daisaku Yamada; Hiroshi Wada; Yoshiaki Fujii; Takahito Sugase; Masaaki Yamamoto; Tomohira Takeoka; et al. (BMC Cancer, 2023)
Abstract Background Duke pancreatic mono-clonal antigen type 2 (DUPAN-II) is a famous tumour maker for pancreatic cancer (PC) as well as carbohydrate antigen 19–9 (CA19-9). We evaluated the clinical implications of DUPAN-II levels as a biological indicator for PC during preoperative chemoradiation therapy (CRT). Methods This retrospective analysis included data from 221 consecutive patients with resectable and borderline resectable PC at diagnosis who underwent preoperative CRT between 2008 and 2017. We focused on 73 patients with elevated pre-CRT DUPAN-II levels (> 230 U/mL; more than 1.5 times the cut-off value for the normal range). Pre- and post-CRT DUPAN-II levels and the changes in DUPAN-II ratio were measured. Results Univariate analysis identified normalisation of DUPAN-II levels after CRT as a significant prognostic factor (hazard ratio [HR] = 2.06, confidence interval [CI] = 1.03–4.24, p = 0.042). Total normalisation ratio was 49% (n = 36). Overall survival (OS) in patients with normalised DUPAN-II levels was significantly longer than that in 73 patients with elevated levels (5-year survival, 55% vs. 21%, p = 0.032) and in 60 patients who underwent tumour resection (5-year survival, 59% vs. 26%, p = 0.039). Conclusion Normalisation of DUPAN-II levels during preoperative CRT was a significant prognostic factor and could be an indicator to monitor treatment efficacy and predict patient prognosis.